Clozapine and concomitant medications: Assessing the completeness and accuracy of medication records for people prescribed clozapine under shared care arrangements. Issue 6 (4th May 2017) - Murphy, Kate; Coombes, Ian; Moudgil, Vikas; Patterson, Susan; Wheeler, Amanda
Abstract: Rationale, aim, and objective: The objective of the study is to assess the completeness and accuracy of medication records held by stakeholders (secondary care, general practice, and community pharmacy) for clozapine consumers managed in a shared care programme. Methods: This was an exploratory, descriptive study examining secondary and primary care medication records in a large, urban, public mental health service setting in Queensland, Australia. Consumers (18‐65 years old) prescribed clozapine under shared care management with capacity to consent were eligible (n = 55) to participate. Information from medication and dispensing records was used by a pharmacist to compile a best possible medication history for each consumer. Discrepancies were identified through reconciliation of stakeholder records with the history. Discrepancies were defined as an omission, addition, or administration discrepancy (difference in dose, frequency, or clozapine brand). Results: Thirty‐five (63.6%) consumers consented for records to be reviewed. Overall, 32 (91.4%) consumers had at least 1 discrepancy in their records with a mean of 4.9 discrepancies per consumer. Of 172 discrepancies, 127 (73.8%) were omissions. Primarily, concomitant medicines were omitted in 19/35 (54%) of secondary care records while clozapine was omitted in 13/32 (40.6%) of community pharmacies records. Conclusions: Discrepancies were highly prevalent in the shared care medication records of clozapine consumers of this service. Where there is incomplete and inaccurate medication information, there is a risk of suboptimal clinical decision making, increasing the likelihood of adverse drug events. This study demonstrates a need for improved documentation and timely access to accurate and complete medication records for shared care stakeholders. Expanding the pharmacist's role in this setting could improve medication accuracy in documentation and related communication.